Pemenuhan Hak dan Kewajiban dalam Masa Syiqoq : Kajian Fiqh Keluarga Islam - Siska Ayu Anggraini (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
This study discusses the fulfillment of the rights and obligations of husbands and wives during the period of syiqoq from the perspective of Islamic law. Syiqoq, which refers to deep conflicts between husband and wife, poses a significant challenge in married life. The purpose of this research is to analyze how Islamic law regulates the fulfillment of rights and obligations during conflict and to offer solutions for its resolution. This study employs a qualitative descriptive approach using literature review methods, analyzing fiqh literature, fatwas from Islamic scholars, and other primary and secondary sources. The findings indicate that despite ongoing disputes, fundamental rights such as maintenance, protection, and housing must still be provided, and obligations like communication and consultation are essential for resolving conflicts. The role of hakam as a third party mediator is also identified as an effective mechanism for resolving syiqoq. The implications of this study provide practical guidance for couples and Islamic legal institutions in addressing marital conflicts fairly and in accordance with Islamic principles while strengthening the understanding of family law dynamics in a modern context.